A component analysis of toilet‐training procedures recommended for young children. Issue 1 (23rd December 2015) - Greer, Brian D.; Neidert, Pamela L.; Dozier, Claudia L.
Abstract : We evaluated the combined and sequential effects of 3 toilet‐training procedures recommended for use with young children: (a) underwear, (b) a dense sit schedule, and (c) differential reinforcement. A total of 20 children participated. Classroom teachers implemented a toilet‐training package consisting of all 3 procedures with 6 children. Of the 6 children, 2 showed clear and immediate improvements in toileting performance, and 3 showed delayed improvements. Teachers implemented components of the training package sequentially with 12 children. At least 2 of the 4 children who experienced the underwear component after baseline improved. Toileting performance did not improve for any of the 8 children who were initially exposed to either the dense sit schedule or differential reinforcement. When initial training components were ineffective, teachers implemented additional components sequentially until toileting performance improved or all components were implemented. Toileting performance often improved when underwear or differential reinforcement was later added.